2018
DOI: 10.1186/s13104-018-3608-y
|View full text |Cite
|
Sign up to set email alerts
|

Institutional support for breastfeeding in Ghana: a case study of University of Education, Winneba

Abstract: ObjectivesThis study explored institutional support for breastfeeding student-mothers in the University of Education, Winneba, Ghana. It also examined challenges associated with combining academic work with breastfeeding and childcare.ResultsFindings show that although the University as an institution does not have any formal system in place to support breastfeeding among student-mothers, it does follow the provisions made for breastfeeding under the maternity protection section of the labor Act (Act, 651) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 17 publications
4
18
0
3
Order By: Relevance
“…Support from husbands and relatives were supportive in coping with stress and burnout arising from work and breastfeeding. This result is consistent with research ndings in Ghana, where family support was supportive of exclusive breastfeeding practice among working mothers [8].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Support from husbands and relatives were supportive in coping with stress and burnout arising from work and breastfeeding. This result is consistent with research ndings in Ghana, where family support was supportive of exclusive breastfeeding practice among working mothers [8].…”
Section: Discussionsupporting
confidence: 92%
“…However, work-breastfeeding tension is experienced differently depending on the type of work a mother does. In some cases, the con ict between work and breastfeeding has led some mothers to withdraw from work or spend less time with babies [8,9]. Also, it has been found that poor recommendations of exclusive breastfeeding from health workers and shorter duration of maternity leave are partly the reasons behind the decline in exclusive breastfeeding at six months [10].…”
Section: Work Breastfeeding and Workplace Support In Ghanamentioning
confidence: 99%
See 2 more Smart Citations
“…Authorities could work with student governments and other student organizations at the various campuses to inform and educate their student bodies about breastfeeding resources and provisions available to them. Anecdotally, WEB (coauthor) has known faculty members and graduate students who hung curtains in office windows or used a small storage closet as space to express milk at one of the participating institutions (American University Washington, 2018; Nkrumah & Gbagbo, 2018; Welek, 2015). Also, particularly undergraduate students have used either the office or lab space of AKA (the lead author) to express their milk.…”
Section: Discussionmentioning
confidence: 99%